2016
DOI: 10.1097/md.0000000000005405
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the maximum rate of pressure rise in the central and peripheral arteries after weaning from cardiopulmonary bypass in pediatric congenital heart surgery

Abstract: The maximum rate of pressure rise (dP/dtmax) in radial artery has been proposed as a noninvasive surrogate of aortic dp/dtmax, reflecting left ventricular (LV) contractility in children. The aim of this study was to investigate relationship between aortic and radial dp/dtmax at weaning from cardiopulmonary bypass (CPB) and usefulness of these indices for estimating postoperative outcomes in pediatric congenital heart surgery.Aortic and radial arterial pressure waveforms were analyzed simultaneously during wean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Our study challenges the previous belief that femoral d P /d t max could be used as a reliable marker of LV systolic function at the bedside. This belief was based on the observed good correlation between LV and arterial d P /d t max during periods of haemodynamic stability [7, 9, 12]. However, correlations alone lack the sufficient value to inform on the responses of femoral d P /d t max to treatments during cardiovascular failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study challenges the previous belief that femoral d P /d t max could be used as a reliable marker of LV systolic function at the bedside. This belief was based on the observed good correlation between LV and arterial d P /d t max during periods of haemodynamic stability [7, 9, 12]. However, correlations alone lack the sufficient value to inform on the responses of femoral d P /d t max to treatments during cardiovascular failure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that measurements of arterial d P /d t max obtained from radial [7, 9] and femoral [7, 10] arterial pressure waveforms were comparable to LV d P /d t max and, in some cases, might be useful for predicting patient outcome [11]. However, conflicting results regarding the comparability of LV d P /d t max and arterial d P /d t max have also been presented in both adults and children [12, 13]. Despite these uncertainties, arterial d P /d t max is most often presented as a marker of LV systolic function in many off-the-shelf haemodynamic monitoring systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Kim et al [19] studied the relationship between arterial dP/dt max from the radial artery, aortic dP/dt max , and selected echocardiographic variables such as LV ejection fraction or LV fractional shortening in children undergoing congenital heart disease surgery. They did not find a significant correlation between arterial dP/dt max and the other variables, and these observations were explained by differences between radial artery and aortic pressure waveforms.…”
Section: Discussionmentioning
confidence: 99%
“…(B) To detect or suspect an RFAPG, several methods can be used, including radial AP waveform analysis, the use of NIBP of the upper extremity,23,39 and ultrasound techniques using two-dimensional measurement and Doppler. Unreliable radial arterial pressure should be suspected if two-dimensional ultrasound measurement of the radial artery diameter is less than 1.8 mm, 10 if the change of pressure over time (dP/dt) of the radial artery does not correlate with cardiac function,6,42 if the estimated dP/dt and the PG calculated from the MR Doppler signal is higher than the radial artery pressure18,43 or if there is no triphasic arterial signal using Doppler interrogation of a radial or brachial artery. Dynamic testing and evaluation of damping coefficient should also always be performed when using an arterial pressure signal 44.…”
mentioning
confidence: 99%